Perception And Implementation Of Islamic Education Evaluation: A Mixed Method Study In Integrated Islamic Schools - Iman Subasman; Philip C van der Westhuizen; Willius Kogoya; Atep Jejen (Jurnal Ilmu Pendidikan, 2025)
Evaluation Islamic education in Integrated Islamic Schools (SIT) faces challenge in ensure integration Islamic values and achievements academic in a way holistic. Research This aiming explore perception stakeholders interest to the evaluation model Islamic education and analyze its implementation. With mixed method approach and convergent parallel design, research This involving 200 respondents through questionnaire quantitative and interview qualitative. Research results show that 85% of respondents own perception positive to the relevance of the evaluation model, especially in support integration Islamic values and formation character students. Respondents with background behind education more height and experience longer teaching shows more appreciation deep to approach This. In conclusion, the evaluation model Islamic education at SIT is understood as instrument strategic For support multidimensional education. Research results This give contribution to theory evaluation Islamic education and offer guide practical For development instrument further evaluation adaptive. Research This beneficial in increase quality evaluation Islamic education, both at the elementary level institution and also policy